Phospho-histone-H3 immunostaining for pulmonary carcinoids: impact on clinical appraisal, interobserver correlation, and diagnostic processing efficiency - Laflamme, Philippe; Mansoori, Babak K.; Sazanova, Olga; Orain, Michèle; Couture, Christian; Simard, Serge; Trahan, Sylvain; Manem, Venkata; Joubert, Philippe (Human pathology, 2020)
Lung carcinoid tumors are classified as either typical or atypical based on the presence of necrosis and the maximum mitotic count per 2 mm2 area. Determining the mitotic count, which is manually conducted on slides stained with hematoxylin and eosin (HE), is time-consuming and subject to high interobserver variability. The objective of this study was to test the sensitivity and specificity of a surrogate mitosis marker, phospho-histone-H3 (PHH3) immunostaining, in the processing of pulmonary carcinoids as compared with the standard HE evaluation. Carcinoid tissue blocks that were available from lung resection specimens were analyzed using HE and PHH3 stains. Two thoracic pathologists and two residents determined the mitotic count on HE and PHH3 stains in accordance with the 2015 WHO guidelines and recorded the time required to complete this task. For both methods, the interobserver agreement among raters for the mitotic count/2 mm2 was assessed by conducting intraclass correlation analyses. We found that for both pathologists and residents, the time required to determine the mitotic count using the PHH3 method was reduced compared with the traditional HE method. Furthermore, residents detected more mitoses/2 mm2 using the PHH3 stain compared with the HE method. More importantly, the PHH3 method yielded better interobserver agreement than the HE method in terms of mitoses/mm2 detection. Overall, our data confirmed that histologic assessments of carcinoid tumors using PHH3 staining provides practical benefits in terms of scoring times, mitosis detection, and reproducibility of mitotic counts. In addition, we found that the benefit was even greater for less experienced pathologists.